Does transvaginal natural orifice transluminal endoscopic surgery affect female sexual function?: a prospective cohort study - Dingyu Xu; Li He; Yonghong Lin; Yayu Zhou; Zhaolin Gong; Qian Zhang; Qiannan Hou; Lu Huang (BMC, 2023)
Abstract Background To evaluate the effect of transvaginal natural orifice transluminal endoscopic surgery (vNOTES) on female sexual function. Methods: The trial was registered at the Chinese Clinical Trial Registry (ChiCTR2100050887, 07/09/2021). In this prospective cohort study, we prospectively analyzed the data of the female sexual function index (FSFI) questionnaire of 130 patients who underwent laparoscopy in Chengdu Women's and Children's Central Hospital due to gynecological benign diseases. The patients were assigned to the vNOTES group and the control group (underwent traditional laparoscopic surgery or transumbilical laparoendoscopic single-site surgery). Results: There were 4 cases dropout in the vNOTES group and 2 cases dropout in the control group. There was no difference in the ages (31.70 ± 5.02 vs. 30.37 ± 5.74, P>0.05), BMI (body mass index, 21.76 ± 3.16 vs. 23.30 ± 2.69, P>0.05), Education level, surgical types, and FSFI scores (22.31 ± 2.25 vs. 21.55 ± 3.38) between the vNOTES group and the control group before surgery. There was no difference in FSFI scores six months postoperation between the vNOTES group and the control group (21.61 ± 3.22 vs. 20.99 ± 3.26, P>0.05), and there was no difference in FSFI scores pre- and six months postoperation in vNOTES group (21.61 ± 3.22 vs. 22.31 ± 2.25, P>0.05). The time to start sexual life after surgery in the vNOTES group was later than that in the control group (39.34 ± 0.71 d versus 37.86 ± 0.69 d, P < 0.05). Conclusions: vNOTES has no significant adverse effect on female sexual function, however, the time to start sexual life after vNOTES is later than that after trans-abdominal laparoscopy.